Safer Tractor Operations for Home and Acreage Owners - Carol J. Lehtola; Charles M. Brown (EDIS, 2003)
This publicaton is intended to point out Safer Tractor Operations for Home and Acreage owners. The principles of safety are the same, whether the tractor is 25 horsepower or 200. This document is CIR 1251,one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published September 2002.